2020
DOI: 10.1177/0300060520941974
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival after cemented versus uncemented total hip arthroplasty for treatment of acute femoral neck fracture: a retrospective study with a mean 10-year follow-up

Abstract: Objective To compare the long-term survivorship and Harris hip scores (HHSs) between cemented total hip arthroplasty (CTHA) and uncemented total hip arthroplasty (UTHA) for treatment of acute femoral neck fractures (FNFs). Methods Data of 224 hips (CTHA, n = 112; UTHA, n = 112) that underwent primary surgery in our medical institution from 2005 to 2017 were retrospectively analysed. The primary endpoint was the risk of all-cause revision. The difference in the risk of all-cause revision between the two groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Parker et al [29] reported a clear advantage of cemented arthroplasties with regard to faster mobilization and reduction of postoperative pain in a systematic review [29]. Furthermore, the rate of aseptic revisions was significantly reduced among cemented hemiarthroplasties and total hip arthroplasties [27,[30][31][32]. For cemented hemiarthroplasties within the first 2 days after surgery, Fenelon et al [33] reported an increased mortality compared to uncemented stems.…”
Section: Discussionmentioning
confidence: 99%
“…Parker et al [29] reported a clear advantage of cemented arthroplasties with regard to faster mobilization and reduction of postoperative pain in a systematic review [29]. Furthermore, the rate of aseptic revisions was significantly reduced among cemented hemiarthroplasties and total hip arthroplasties [27,[30][31][32]. For cemented hemiarthroplasties within the first 2 days after surgery, Fenelon et al [33] reported an increased mortality compared to uncemented stems.…”
Section: Discussionmentioning
confidence: 99%
“…The revision rates of the uncemented prosthesis were significantly higher (66/444 vs 27/ 441) which was seen consistently in all studies reporting revision rates. 1,11,14,15 This analysis suggests that cemented fixation gives favorable results in elderly patients with neck or femur fractures, as demonstrated by all studies included in the analysis. In contrast, some previous studies did not find a difference in the overall mortality rates, complications, and functional and radiological results, which were similar in patients undergoing an uncemented with those undergoing a cemented THA performed for hip fracture.…”
Section: Discussionmentioning
confidence: 74%
“…Four studies compared HHS between groups of more than 5 years. 1,11,13,15 The HHS score was seen to be more in the cemented group in comparison with the uncemented group and was statistically significant (MD ¼ 5.20; CI ¼ À6.68 to À3.73; P < 0.00001) (Figure -2).…”
Section: Harris Hip Score >5 Yearsmentioning
confidence: 95%
See 1 more Smart Citation
“…To date, few studies on converting failed PFNAs provide effective consensus recommendations for reducing or avoiding mechanical failures [ 30 , 31 ]. Lack of the design and material characteristics of THR implants can lead to remarkable distinctions in comparisons between studies [ 32 , 33 ]. The long-term outcomes of hybrid THR for elderly individuals remain controversial [ 21 , 27 ].…”
Section: Discussionmentioning
confidence: 99%